Systematic literature review on recycling waste cooking oil using public service announcement / Nurul Najihah Abd Raffik, Azahar Harun and Farihan Zahari - Abd Raffik, Nurul Najihah; Harun, Azahar; Zahari, Farihan (Faculty of Art and Design, 2024)
Cooking oil has attained significant importance and is regularly consumed on a global scale, encompassing both beneficial as well as negative practices. Nevertheless, the management of waste cooking oil (WCO) has been implemented through various methods that have resulted in significant environmental concerns. This article undertakes an analysis of the public service announcement (PSA) campaign aimed at promoting the management of waste cooking oil. This study employs a qualitative methodology and utilises a systematic literature review (SLR) approach to identify relevant scholarly articles pertaining to waste cooking oil. The acquired data is subjected to analysis through the use of a document analysis methodology in order to elucidate the significant information derived from the journal. The screening methodology has identified a total of four (4) articles published between 2019 and 2023 that are relevant to the investigation of the utilisation of public service announcements in the promotion of waste cooking oil. The findings indicate a significant dearth of prior scholarly investigations concerning public service announcements related to the recycling of waste cooking oil. It is strongly advised that future research be conducted to investigate the influence of public service announcements (PSAs) on waste cooking oil, particularly in the context of Malaysia.